DDA 농업협상 진전 상황에 따른 농업부문 영향분석 - 임송수 (한국농촌경제연구원, 2006)
The purposes of this study are to draw up implications from the agricultural proposals made by the United States, the European Union, and the Group of 20 (G20) countries for the Doha Round negotiations, to analyze spillover effects on domestic agriculture, and then to propose recommendations for establishing the Country Schedule (C/S) and indicate directions for agricultural policies under the new WTO regime. The implications drawn out by analyzing market access scenarios can be summarized as follows: First, the U.S proposal will bring Korean tariffs to deeper cuts than the EU and G20 proposals. Second, designation of sensitive products would partially contribute to alleviate negative effects of tariff cuts. However, substantial designation of special products, above all, is given priority to minimize negative effects of tariff cuts. Especially the negative effects of tariff capping would be minimized by securing sufficient numbers of special products. The results of domestic support scenarios are as follows: Under the developing country status, the overall base level of the Overall Trade Distorting Support (OTDS) is subject to a substantial reduction of up to 47% at maximum, and the sum of AMS plus de minimis (DM) plus Blue Box (BB) is reduced by 48%. However under the developed country status, the OTDS is declined by maximum 70% and the sum of AMS, DM, and BB is reduced by 78%. Therefore, the OTDS does not constrain the utilization of domestic supports on the basis of the end of the implementation period of the Doha Development Round. The KREI-ASMO and partial equilibrium models are applied to forecast modality effects on domestic agriculture. Agricultural income including direct payments for rice would be subject to lower cuts than in the case of no direct payment for rice. Namely, the direct payment for rice would be expected to contribute to attenuate decreases of farm income during the DDA round. And the analysis of a partial equilibrium model shows that the production values of beef, pig, pepper, garlic, etc. would be subject to deeper cuts than those of other commodities. Taking a higher level of market opening into consideration, Korean agriculture needs lower reduction obligations and additional transition periods in implementing the WTO rules. After submitting the country schedule on the basis of modalities, we need to conduct bilateral negotiations with the countries concerned. Hence, we should concentrate our efforts to maintain the developing country status in bilateral negotiations. Now, while the infrastructure and international competitiveness of domestic agriculture are still poor, domestic agriculture has come to face drastic changes and crises as it has to fully open its agricultural market. Korean agricultural policies have been centered on supporting rice prices, but these policies need to be redirected to strengthen government services or expand directly paid subsidies. Therefore, to effectively make preparations for a new era of openness, it is imperative to reform agricultural policies.